2023
DOI: 10.1111/desc.13443
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive mechanisms of co‐occurring math difficulties in dyslexia: Differences in executive function and visuospatial processing

Rebecca A. Marks,
Courtney Pollack,
Steven L. Meisler
et al.

Abstract: Children with dyslexia frequently also struggle with math. However, studies of reading disability (RD) rarely assess math skill, and the neurocognitive mechanisms underlying co‐occurring reading and math disability (RD+MD) are not clear. The current study aimed to identify behavioral and neurocognitive factors associated with co‐occurring MD among 86 children with RD. Within this sample, 43% had co‐occurring RD+MD and 22% demonstrated a possible vulnerability in math, while 35% had no math difficulties (RD‐Onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 124 publications
(158 reference statements)
1
2
0
Order By: Relevance
“…Similar to other studies, our findings also support the correlated liability model, according to which the comorbid RDMD group displays an additive combination of deficits in working memory in the RD and MD groups [25][26][27]33,34]. This perspective is also corroborated by the findings of neuroimaging studies, as no distinct neural activation patterns specific to RDMD have been identified [56], at least not in tasks related to phonological working memory [16]. In the ICD-10, a mixed disorder of scholastic skills is categorized as a subtype within specific reading disorders, and this relevant classification still requires to be discussed in terms of etiology [57].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Similar to other studies, our findings also support the correlated liability model, according to which the comorbid RDMD group displays an additive combination of deficits in working memory in the RD and MD groups [25][26][27]33,34]. This perspective is also corroborated by the findings of neuroimaging studies, as no distinct neural activation patterns specific to RDMD have been identified [56], at least not in tasks related to phonological working memory [16]. In the ICD-10, a mixed disorder of scholastic skills is categorized as a subtype within specific reading disorders, and this relevant classification still requires to be discussed in terms of etiology [57].…”
Section: Discussionsupporting
confidence: 91%
“…The phonological loop is usually assessed with simple span tasks (e.g., the WISC-R digit span forward task), central executive with complex span tasks (e.g., the Daneman-Carpenter listening or reading span task), and updating with N-back tasks. Because the results concerning the visuospatial sketchpad are clear (i.e., they show that it is specifically impaired in children with mathematics difficulties [16][17][18]), we will not discuss them further.…”
Section: Introductionmentioning
confidence: 99%
“…Using mostly lab-based cognitive neuroscience approaches (but see Janssen et al, 2021), educational neuroscience researchers have examined the cognitive and neural bases of school-relevant skills. Not meant to impact the classroom directly, this research has elucidated the neurocognitive mechanisms that underlie learning, such as basic processes in numerical cognition (Pollack & Price, 2019, the relation between math and reading (Pollack et al, 2021;Pollack & Ashby, 2018), and the connection of both with executive functioning (Marks et al, 2023). Connecting to classroom learning, MBE work has advanced understandings of education challenges across levels of analysis.…”
Section: Courtney Pollackmentioning
confidence: 99%